1997
DOI: 10.1039/a701142c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel dansyl appended cyclodextrins. Self-inclusion and sensor properties

Abstract: The synthesis o f three dansyl appended cyclodextrin derivatives, differing in the spacer length between cyclodextrin and the dansyl moiety, is described. In compound 4 the fluorophore is directly attached to the cyclodextrin. Com pound 5 contains an ethyl spacer and compound 6 a triethylene glycol spacer. These com pounds are designed to detect neutral organic guest molecules like cyclohexanol and adamantanecarboxylic acid in water by fluorescence spectroscopy. At neutral pH none of the compounds is sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 21 publications
3
34
1
Order By: Relevance
“…Protonation of the dansyl moieties: It is known [4] that the amino group of the dansyl chromophoric unit can be quantitatively protonated by trifluoromethylsulfonic (triflic) acid in organic solvents, with strong changes in the absorption and emission spectra. We have found that both reference compound Da and the dansyl moieties of KN(Ao) 2 (Da), KN(Ao)(Da) 2 , and KN(Da) 3 exhibit such spectral changes.…”
Section: Resultsmentioning
confidence: 99%
“…Protonation of the dansyl moieties: It is known [4] that the amino group of the dansyl chromophoric unit can be quantitatively protonated by trifluoromethylsulfonic (triflic) acid in organic solvents, with strong changes in the absorption and emission spectra. We have found that both reference compound Da and the dansyl moieties of KN(Ao) 2 (Da), KN(Ao)(Da) 2 , and KN(Da) 3 exhibit such spectral changes.…”
Section: Resultsmentioning
confidence: 99%
“…We also synthesized the guests: 2-(p-(2'-hydroxyethyl)anilino)-6-naphthalene sulfonate (6) and 2-(p-(3',6',9'-trioxa-11'-hydroxyundecane)anilino)-6-naphthalene sulfonate (7), for which we propose the abbreviations ENS and TENS, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Monotosylation of triethyleneglycol using NaH as a base gave 34, [7] which was protected with a triphenylmethyl (Trt) group. The protected compound 35 [7] was allowed to react with the alkoxy anion of 2-(4'-aminophenyl)ethyl alcohol to give 36, which was deprotected and treated with 6-amino-2-naphtha- NMR studies: The one-dimensional 13 C and 1 H NMR spectra of compounds 2 and 4 have been described in a preliminary communication. [4] The full assignment of the high-resolution proton spectrum (600 MHz) of 2 was published by us recently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of using cyclodextrins for sensor purposes, by appending a fluorescent receptor molecule, has been studied by Ueno [6] and others. [7,8] In this type of system, the generation of a signal is based on the competition for the cyclodextrin cavity between the covalently attached fluorophore and an added guest. In the absence of a guest, the fluorophore partially resides inside the cavity.…”
Section: Introductionmentioning
confidence: 99%